Earth: the restless planet. - National Geographic Society (U.S.) (National Geographic Society, 1973)
Examines the characteristics of three different volcanoes--Hawaii's Kilauea, Mt. Etna in Sicily, and Nyiragongo in Zaire.
Also issued as videocassette.
Edited from the motion picture entitled The violent earth.
With teacher's guide and collateral materials.
Keywords: Kilauea Volcano (Hawaii); Etna, Mount (Italy); Nyiragongo (Congo)